2021
DOI: 10.1186/s12885-021-08892-4
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis regulators, especially SQLE, play an important role in prognosis, progression and immune environment of breast cancer

Abstract: Background Ferroptosis, a new form of programmed cell death, has great potential for cancer treatment. However, the roles of ferroptosis-related (FR) genes in breast cancer (BC) remain elusive. Materials and methods Using TCGA database, a novel FR risk signature was constructed through the Lasso regression analysis. Meanwhile, its prognostic value was assessed by a series of survival analyses. Besides, a nomogram was constructed to predict the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Some of the strongest gains in 8q included PHF20L1, NRDG1, MYC and SQLE . In the context of breast cancer, PHF20L1 overexpression promotes tumorigenesis and is associated with higher grades 54 , NRDG1 overexpression is associated with metastasis and mortality 55 , MYC is a classical amplified oncogene 56 and SQLE overexpression promoted proliferation and invasiveness 57 . The luminal B subtype is an aggressive breast cancer subtype, thus consistent with these amplifications 58 .…”
Section: Resultsmentioning
confidence: 99%
“…Some of the strongest gains in 8q included PHF20L1, NRDG1, MYC and SQLE . In the context of breast cancer, PHF20L1 overexpression promotes tumorigenesis and is associated with higher grades 54 , NRDG1 overexpression is associated with metastasis and mortality 55 , MYC is a classical amplified oncogene 56 and SQLE overexpression promoted proliferation and invasiveness 57 . The luminal B subtype is an aggressive breast cancer subtype, thus consistent with these amplifications 58 .…”
Section: Resultsmentioning
confidence: 99%
“…SQLE is the key rate‐limiting enzyme in cholesterol biosynthesis and a target of fungicides and increasing interest in human health and disease 16 . Previous studies revealed that, as a ferroptosis regulator, SQLE was associated with the proliferation and metastasis of breast cancer 19 . Tumor‐related genes usually show two sides, inhibiting or promoting cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, human SQLE has attracted more and more attention as a bonafide oncogene and a target of tumor treatment 17,18 . As a ferroptosis regulator, SQLE was identified as a crucial cancer‐promoting gene in the breast cancer 19 . Moreover, previous studies indicated that SQLE reduction disrupted the GSK3β/p53 complex, and helped colorectal tumor cells surmount constraints by evoking the epithelial‐mesenchymal transition (EMT) process required to produce tumor stem cells 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that infiltrating immune cells can be isolated from tumors suggesting that tumor immune infiltration is a crucial biological process of cancers [ 10 ]. Further, many studies indicate that ferroptosis regulators play an important role in immune environment of cancers including breast cancer [ 11 ], hepatocellular carcinoma [ 12 ], and others. However, the ferroptosis related genes of tumor immune infiltration in PAAD remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%